My journey with Nidān: looking back and looking forward - Penumala, Pratap Kumar (Nidān, 2023)
It is a truism that political processes and academic enterprises are inherently linked to one another. I cannot think of any academic enterprise that is free of politics of the state. The story of my journey with Nidān is underlined by the above assumption. I could hardly separate my academic career from the life of Nidān as a journal as it has stayed with me (perhaps I have stayed with it) for the best part of my academic career. Therefore, my journey with Nidān could hardly be told without my academic journey in South Africa.